Evaluasi Kondisi Perkerasan Jalan Bundaran Waru Menggunakan Metode PCI, SDI, dan Roadroid Berbasis Smartphone - Irfan Zhain; Prathita Muti'a Yuzaeva; Rizki Firman Alamsyah (Jurnal Karajata Engineering, 2026)
Evaluating road damage using Pavement Condition Index, Surface Distress Index, and International Roughness Index methods is generally difficult to implement in roundabout areas due to high traffic volumes and surveyor safety risks. Limited access to such congested road sections often hinders the accuracy and efficiency of conventional pavement condition data collection. Therefore, this study utilizes a digital road distress assessment application as an alternative solution that is safer, more efficient, and accurate without disrupting the existing traffic flow. A quantitative research method was employed to compare the standard evaluation results of PCI and SDI methods against the digital application-based method, which generates IRI values. Data collection focused on high-volume roundabout sections through field surveys and data analysis. The results indicate that loose aggregate and patching were identified as the most dominant distress types in the roundabout area. A locally significant condition was detected, particularly in the STA 0+300 to 0+400 segment, which exhibited poor values. In this specific segment, the structural evaluation yielded an SDI value of 115, while the PCI score dropped to 47, indicating a fair condition. This decline in functional performance aligns with the Roadroid application records, which showed a sharp increase in the IRI value, reaching 9.02. Based on the analysis of these various assessment methods, specific road maintenance recommendations per segment, such as routine or periodic maintenance, are provided.